Left atrial appendage occlusion for stroke prevention in patients with atrial fibrillation: indications diversity and future perspectives. Issue 1 (March 2016) - Tzikas, A.; Lewalter, T.
Abstract: Left atrial appendage occlusion (LAAO) is a promising alternative to oral anti‐coagulation in patients with non‐valvular atrial fibrillation. Recently, four‐year results of PROTECT‐AF demonstrated superiority of LAAO in all‐cause mortality and stroke reduction compared to optimal medical treatment with warfarin. In this new era, it is important to identify the patients who would benefit more from LAAO and offer them priority for treatment. Answer questions and earn CME: https://wileyhealthlearning.com/Activity2/4193475/Activity.aspx